The ghost theatre : a novel - Osman, Mat, 1967- (The Overlook Press, an imprint of ABRAMS, 2023)
"London, 1601--a golden city soon to erupt in flames. Shay is a messenger-girl, falconer, and fortune teller who sees the future in the patterns of birds. Nonesuch is the dark star of the city's fabled Blackfriars Theatre, where a cast of press-ganged boys perform for London's gentry. When the pair meet, Shay falls in love with the performances--and with Nonesuch himself. As their bond deepens, they create the Ghost Theatre, an underground troupe that performs fantastical plays in the city's hidden corners. As their fame grows the troupe fans the flames of rebellion among the city's outcasts, and the lovers are drawn into the dark web of the Elizabethan court. Embattled, with the plague on the rise throughout the country, the Queen seeks a reading from Shay, a moment which unleashes chaos not only in Shay's life, but across the whole of England too" -- Inside jacket.